Implementing child-friendly school principles in vocational curriculum, pedagogy, and assessment: A qualitative case study - Jumadi Jumadi; Achmad Abdul Azis; Luh De Liska; M. Tahir Malik; Ni Made Wulan Sari Sanjaya; La Ode Amril (Jurnal Pendidikan Vokasi, 2026)
Creating safe, inclusive, and participatory learning environments has become a critical challenge in Technical and Vocational Education and Training (TVET), which is expected to develop not only students’ occupational competencies but also their character. However, empirical evidence regarding the implementation of Child-Friendly School (CFS) principles in curriculum, pedagogy, and assessment within vocational secondary education remains limited. This study aimed to explore the implementation of the Child-Friendly School approach at SMK Negeri 1 Makassar, Indonesia. A qualitative case study design was employed, involving 18 informants: one principal, two vice principals, eight teachers, five students, and two parents. Data were analyzed through iterative qualitative coding and thematic development, following the data condensation, data display, and conclusion drawing and verification procedures proposed by Miles, Huberman, and Saldaña. NVivo 14 was used to facilitate data management and analysis. The trustworthiness of the findings was established through source and method triangulation, member checking, and peer debriefing. The findings revealed three major innovations: (1) the systematic integration of child-friendly values into the curriculum and school programs; (2) the implementation of participatory pedagogy through project-based, collaborative, and reflective learning; and (3) the adoption of character-oriented assessment using reflective journals, behavioral observations, and narrative feedback. The implementation was supported by government policies, strong school leadership, teacher commitment, and the active participation of parents and the wider community, while limited infrastructure, diverse student characteristics, and insufficient teacher competence remained significant challenges. Overall, the findings suggest that, within the context of the case examined, Child-Friendly School principles provide a contextually relevant framework for integrating humanistic values into vocational curriculum, pedagogy, and assessment.